A kind of high strength thermal insulation mortar and preparation method thereof

By using functional phase change materials in insulation mortar, combination of vitrified microbeads, mineral fillers and nanomontmorillonite, the existing insulation mortar is easily cracked, hollowed out and fall off during construction, and the insulation performance, strength and durability of the mortar are improved.

CN118084425BActive Publication Date: 2025-04-18QINGDAO WANXING BUILDING MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410200515.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-23
Publication Date
2025-04-18
Estimated Expiration
2044-02-23

AI Technical Summary

Technical Problem

The existing insulation mortar is prone to cracking, hollowing and falling off during construction, with average strength and durability, and low construction efficiency.

Method used

Functional phase change materials are used in combination with vitrified microbeads, mineral fillers and nanomontmorillonite. The functional phase change materials are obtained by vacuum impregnating the composite aggregate in the melting liquid of polyvinyl alcohol and stearyl alcohol.

Benefits of technology

It improves the insulation performance, strength and durability of the mortar, avoids cracking, hollowing and falling off, and ensures the construction quality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high-strength thermal insulation mortar and a preparation method thereof, and belongs to the technical field of building materials. The high-strength thermal insulation mortar comprises the following raw materials: silicate cement, vitrified microspheres, mineral fillers, functionalized phase change materials, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent, retarder and water. Among them, the functionalized phase change material is obtained by vacuum impregnating a composite aggregate in a molten liquid of polyvinyl alcohol and stearyl alcohol, and the composite aggregate comprises nano-titanium dioxide and pre-treated aluminum silicate fiber aerogel. The thermal insulation mortar prepared by the present invention has the characteristics of high strength, good durability, excellent thermal insulation effect, and will not have problems of cracking, hollowing, and falling off when used in building construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a high-strength thermal insulation mortar and a preparation method thereof. Background Art

[0002] As an important building material, thermal insulation mortar plays a key role in improving building energy efficiency, saving energy and reducing consumption. The preparation of this mortar uses lightweight materials as aggregates, cement as a binder, and certain additives are added and mixed by stirring. Due to the use of lightweight aggregates, thermal insulation mortar is not only easy to use in construction, but also reduces the load of the building structure, realizing the lightweight design of the entire building. The thermal insulation mortar ensures that the mortar has good thermal insulation and durability through the scientific ratio of raw materials such as cement, lightweight aggregates and additives. Common thermal insulation mortars include vitrified microsphere type, expanded vermiculite type and expanded perlite thermal insulation mortar, among which the comprehensive performance of vitrified microsphere type thermal insulation mortar is relatively excellent. The application field of thermal insulation mortar is wide, including external wall insulation, internal wall insulation, external and internal insulation of the exterior wall, roof insulation and geothermal insulation layer, etc. This provides a variety of options for the design of building energy-saving systems, which can be flexibly configured according to the building structure and needs to provide effective thermal insulation effects for the building.

[0003] Chinese patent CN201310676389.7 discloses a novel thermal insulation mortar, which is made from the following raw materials: calcium carbonate, talcum powder, fly ash, cement, gypsum, vitamins, oxidized starch, sodium dodecyl sulfate, clove oil, sodium α-olefin sulfonate, rosin, silica fume, caustic soda, sodium diacetate, sodium dihydrogen phosphate, polystyrene foam particles and composite fillers. The thermal insulation mortar is evenly dispersed and has good thermal insulation effect. Chinese patent CN201711450097.6 discloses a method for preparing thermal insulation mortar, comprising the following steps: silicate cement, fly ash, limestone powder, polystyrene particles, bentonite, thickener, double fly powder, tackifier, carboxyethyl methyl cellulose, sodium dodecyl sulfate, calcium fluoride, styrene maleic anhydride copolymer or silicone-polyurethane copolymer, sodium carbonate are mixed and stirred to form the thermal insulation mortar, which can reduce the dry apparent density and thermal conductivity and improve the thermal insulation performance. Chinese patent CN201410332864.3 discloses a method for preparing a novel thermal insulation mortar, comprising the following steps: mixing cryolite powder, anthophyllite powder and barium sulfate, calcining, cooling and grinding to obtain component A, crushing camellia seed cake and cottonseed cake to obtain component B, mixing component A and component B with the remaining raw materials of cement, konjac glucomannan, potassium sodium tartrate, sodium lauryl sulfate, expanded vitrified microspheres, gelatin and composite additives to obtain a thermal insulation mortar with a wide range of raw materials, low cost and good thermal insulation effect. However, the above-mentioned thermal insulation mortar is prone to cracking and hollowing, and its strength and durability are also average, and the construction efficiency is low. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a high-strength thermal insulation mortar, which is used in combination with a functionalized phase change material prepared by a specific method and vitrified microspheres, mineral fillers and nano-montmorillonite, wherein the functionalized phase change material is obtained by vacuum impregnating a composite aggregate in a melt of polyvinyl alcohol and stearyl alcohol, and the composite aggregate includes nano-titanium dioxide and pre-treated aluminum silicate fiber aerogel, which further improves the thermal insulation performance, strength and durability of the mortar in building construction applications, and avoids the problems of cracking, hollowing and falling off. The present invention also provides a preparation method of the above-mentioned high-strength thermal insulation mortar.

[0005] The technical solution adopted by the present invention is:

[0006] A high-strength thermal insulation mortar, comprising the following raw materials:

[0007] Portland cement, vitrified microspheres, mineral fillers, functional phase change materials, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent, retarder and water.

[0008] Preferably, the mineral filler consists of at least two of talc, microsilica powder and fly ash.

[0009] Preferably, the mineral filler is composed of talcum powder, microsilica powder and fly ash in a weight ratio of 1:1-3:1-3.

[0010] The thermal insulation mortar of the present invention improves the thermal insulation performance of the mortar while ensuring the strength and bonding performance of the mortar through the unique raw material combination of silicate cement, vitrified microspheres, mineral fillers, functionalized phase change materials, nano-montmorillonite and dispersible latex powder. Among them, the incorporation of nano-montmorillonite can increase the structural stability of the mortar, improve its static yield stress, and resist deformation; the incorporation of dispersible latex powder can effectively improve the construction and workability of the mortar, and assist in improving the bonding performance of the mortar; the talcum powder, microsilica powder and fly ash in the mineral filler synergistically exert the micro-aggregate effect, wrap the surface of the vitrified microspheres, fill the gaps in the mortar slurry, increase its density and homogeneity, and improve the strength and bonding performance of the mortar. In addition, the above-mentioned mineral fillers also enhance the plasticity of the mortar, making it less likely to have hollowing, falling off, and cracking problems, thereby ensuring the construction quality.

[0011] Preferably, the preparation method of the functionalized phase change material is:

[0012] D1: mixing aluminum silicate fiber aerogel and N-[(3-trimethoxysilyl)propyl]ethylenediaminetriacetic acid for ball milling, then adding them into water for ultrasonic treatment, centrifuging them after the end, and freeze-drying them to obtain pre-treated aluminum silicate fiber aerogel;

[0013] D2: titanium tetrachloride and ethanol aqueous solution are mixed, and then ammonia water is added dropwise, heated and stirred, cooled to room temperature, and then the pre-treated aluminum silicate fiber aerogel is added for ultrasonic treatment. After the end, it is allowed to stand, concentrated under reduced pressure to recover ethanol, and freeze-dried to obtain a composite aggregate;

[0014] D3: Mix polyvinyl alcohol and stearyl alcohol and perform vacuum melting, then add composite aggregate and perform vacuum impregnation, and then cool to room temperature to obtain the functionalized phase change material.

[0015] Furthermore, the present invention uses a combination of polyvinyl alcohol and stearyl alcohol as a phase change material, and uses nano-titanium dioxide hybrid aluminum silicate fiber aerogel as a composite aggregate for encapsulation. The obtained functionalized phase change material has good compatibility and thermal stability. Adding it to the thermal insulation mortar can not only improve the thermal insulation performance of the mortar, but also improve the strength and fire resistance of the mortar. Specifically:

[0016] The invention firstly mixes siloxane N-[(3-trimethoxysilyl)propyl]ethylenediaminetriacetic acid with a polycarboxyl structure and aluminum silicate fiber aerogel with a three-dimensional network structure, and sequentially performs ball milling and ultrasonic treatment to obtain a pre-treated aluminum silicate fiber aerogel grafted with polycarboxyl siloxane; then, active groups such as carboxyl groups on the surface of the aerogel are cross-linked with hydroxyl groups in titanium sol through hydrogen bonding, and freeze-dried to form a stable hybrid aerogel composite aggregate. The composite aggregate has a large specific surface area and not only has the thermal conductivity of the aluminum silicate fiber aerogel, but also has the advantages of high thermal conductivity, good thermal conductivity, and good thermal conductivity. It has the advantages of low conductivity and good thermal stability (the aluminum silicate fiber aerogel with a three-dimensional pore structure in the composite aggregate can form a barrier in the mortar, reduce heat transfer, and assist in enhancing the thermal insulation effect), and can also play a skeleton support role and has excellent mechanical properties; finally, the composite aggregate is placed in molten polyvinyl alcohol and stearyl alcohol for vacuum impregnation, so that the phase change material can effectively enter the pores of the composite aggregate and bond with the hybrid aerogel. The obtained functionalized phase change material not only has good thermal stability, but also has excellent thermal insulation properties and mechanical strength.

[0017] Preferably, the preparation method of the functionalized phase change material is:

[0018] D1: 10-15 parts by weight of aluminum silicate fiber aerogel and 3-6 parts by weight of N-[(3-trimethoxysilyl)propyl]ethylenediaminetriacetic acid are mixed, and ball milled at 500-800 rpm for 10-15 hours; then added to 80-120 parts by weight of water, ultrasonically treated for 1-2 hours, centrifuged after the end, and freeze-dried to obtain the pre-treated aluminum silicate fiber aerogel;

[0019] D2: 1-5 parts by weight of titanium tetrachloride and 100-300 parts by weight of ethanol aqueous solution are mixed, and then 2-6 parts by weight of ammonia water are added dropwise, and stirred at 70-75° C. for 1-2 hours. After the stirring, the mixture is cooled to room temperature, and then 10-15 parts by weight of pretreated aluminum silicate fiber aerogel is added, and ultrasonic treatment is performed for 0.5-2 hours. After the stirring, the mixture is allowed to stand for 10-15 hours, and ethanol is recovered by vacuum concentration and freeze-drying to obtain a composite aggregate;

[0020] D3: 5-10 parts by weight of polyvinyl alcohol and 2-5 parts by weight of stearyl alcohol are mixed, heated to melt under vacuum conditions, and then 2-8 parts by weight of composite aggregate are added, vacuum impregnated for 1-5 hours, and then cooled to room temperature to obtain the functionalized phase change material.

[0021] Preferably, in step D1, the ball milling medium is 1-5 mm zirconia balls, and the ball-to-material ratio is 10-15:1.

[0022] Preferably, the conditions for ultrasonic treatment in step D1 are: 300-600W, 20-50kHz.

[0023] Preferably, the conditions for ultrasonic treatment in step D2 are: 300-600W, 20-50kHz.

[0024] Preferably, the mass percentage concentration of the ethanol aqueous solution in step D2 is 85-95%.

[0025] Preferably, the mass percentage concentration of the ammonia water in step D2 is 23-27%.

[0026] Preferably, the vacuum impregnation conditions in step D3 are: 0.05-0.1 MPa, 50-65°C.

[0027] Preferably, a high-strength thermal insulation mortar comprises the following raw materials:

[0028] 30-80 parts by weight of silicate cement, 30-80 parts by weight of vitrified microspheres, 20-50 parts by weight of mineral filler, 1-10 parts by weight of functionalized phase change material, 0.5-5 parts by weight of nano-montmorillonite, 0.1-1.5 parts by weight of dispersible latex powder, 0.05-0.5 parts by weight of air entraining agent, 0.05-0.5 parts by weight of water retaining agent, 0.05-0.3 parts by weight of retarder and 50-150 parts by weight of water.

[0029] Preferably, a high-strength thermal insulation mortar comprises the following raw materials:

[0030] 40-60 parts by weight of silicate cement, 50-70 parts by weight of vitrified microspheres, 30-40 parts by weight of mineral filler, 3-7 parts by weight of functionalized phase change material, 1-3 parts by weight of nano-montmorillonite, 0.5-1 parts by weight of dispersible latex powder, 0.2-0.4 parts by weight of air entraining agent, 0.1-0.3 parts by weight of water retaining agent, 0.1-0.2 parts by weight of retarder and 90-100 parts by weight of water.

[0031] Preferably, the air entraining agent is at least one of sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, sodium rosin acid, and sodium α-olefin sulfonate.

[0032] Preferably, the water retaining agent is at least one of hydroxypropyl methylcellulose ether, maltodextrin, starch ether, methylcellulose, and hydroxyethyl methylcellulose ether.

[0033] Preferably, the retarder is at least one of sodium gluconate, sodium citrate, tartaric acid and calcium gluconate.

[0034] The present invention also discloses a method for preparing the high-strength thermal insulation mortar, which specifically comprises the following steps:

[0035] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, functional phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are uniformly mixed, and then water is added and stirred at a speed of 50-100 rpm for 5-15 minutes to obtain the high-strength thermal insulation mortar.

[0036] Beneficial effects of the present invention:

[0037] 1. The thermal insulation mortar of the present invention improves the thermal insulation performance of the mortar while ensuring the strength and bonding performance of the mortar through the unique raw material combination of silicate cement, vitrified microspheres, mineral fillers, functionalized phase change materials, nano-montmorillonite and dispersible latex powder. Among them, the incorporation of nano-montmorillonite can increase the structural stability of the mortar, improve its static yield stress, and resist deformation; the incorporation of dispersible latex powder can effectively improve the construction and workability of the mortar, and assist in improving the bonding performance of the mortar; the talcum powder, microsilica powder and fly ash in the mineral filler synergistically exert the micro-aggregate effect, wrap the surface of the vitrified microspheres, fill the gaps in the mortar slurry, increase its density and homogeneity, and improve the strength and bonding performance of the mortar. In addition, the above-mentioned mineral fillers also enhance the plasticity of the mortar, making it less likely to have hollowing, falling off, and cracking problems, thereby ensuring the construction quality.

[0038] 2. The thermal insulation mortar of the present invention is also mixed with a functionalized phase change material prepared by a specific method, wherein the functionalized phase change material is obtained by vacuum impregnating a composite aggregate in a molten solution of polyvinyl alcohol and stearyl alcohol, and the composite aggregate includes nano-titanium dioxide and pre-treated aluminum silicate fiber aerogel, which further improves the thermal insulation performance, strength and durability of the mortar in building construction applications. DETAILED DESCRIPTION

[0039] The above-mentioned invention contents of the present invention are further described in detail below in conjunction with specific implementation methods. The embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the contents of the present invention and implement them accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

[0040] Portland cement, using 42.5 ordinary Portland cement.

[0041] Talc, model: H-800, Nanjing Chendong New Materials Co., Ltd.

[0042] Microsilica fume, model: KX-12, silica content 95%, Hebei Kexu Building Materials Co., Ltd.

[0043] Fly ash, item number: 100023, Lingshou County Ruicheng Mineral Products Co., Ltd.

[0044] Vitrified microspheres, item number: 0275, density: 120-200g / cm 3 , Zhongshan Rongsheng Energy Saving Technology Co., Ltd.

[0045] Nano-montmorillonite, model: WSG-PN06, content: 98%, Shanghai Wanzhao Fine Chemical Co., Ltd.

[0046] Dispersible latex powder, model: LJ5003, bulk density: 300-500g / L, Renqiu Lanke Environmental Protection Technology Co., Ltd.

[0047] Polyvinyl alcohol, product number: PVA100-27(1799), Inner Mongolia Shuangxin Environmental Protection Materials Co., Ltd.

[0048] The aluminum silicate fiber aerogel used in the embodiment is prepared according to the method described in paragraphs 0040-0044 of the specification of patent CN116948390B, and the specific steps are as follows:

[0049] 5 g of aluminum silicate fiber was immersed in a sodium carbonate solution with a mass fraction of 1.5%. After 3 hours, the material was centrifuged out, washed and vacuum dried to obtain pretreated aluminum silicate fiber.

[0050] 3.2 g of pretreated aluminum silicate fiber was mixed with a mixed solution of anhydrous ethanol and purified water in a volume ratio of 3:1, and ultrasonically dispersed to form a uniform dispersion, and 5 g of 3-(methacryloyloxy)propyltrimethoxysilane was added. After the addition was completed, the temperature was raised to 65° C., stirred for 6 h, cooled and discharged, and the solid material was separated by centrifugation to obtain modified aluminum silicate fiber;

[0051] 3 g of modified aluminum silicate fiber was uniformly dispersed in a mixed solution of anhydrous ethanol and purified water in a volume ratio of 1:1, and then 6.5 g of hydroxyethyl methacrylate, 0.2 g of N,N-methylene acrylamide and 0.01 g of benzoyl peroxide were added and stirred evenly. After being kept warm and stirred at 80° C. for 24 hours, the solid material was separated to obtain a precursor;

[0052] 2 g of the precursor was dispersed in purified water, 1 g of sodium dodecyl sulfate was added, and after mixing evenly, cyclohexane was continued to be added and stirred to form a stable emulsion. The mixture was stirred and emulsified at 55 °C for 30 min, and then 0.5 g of benzoyl peroxide was added. After the addition, the temperature was raised to 75 °C. After stirring for 8 h, the material was separated, washed and freeze-dried to obtain aluminum silicate fiber aerogel.

[0053] Example 1

[0054] A high-strength thermal insulation mortar, comprising the following raw materials:

[0055] 50 parts by weight of silicate cement, 60 parts by weight of vitrified microspheres, 35 parts by weight of mineral fillers, 5 parts by weight of functionalized phase change materials, 2 parts by weight of nano-montmorillonite, 0.8 parts by weight of dispersible latex powder, 0.3 parts by weight of air entraining agent sodium dodecylbenzene sulfonate, 0.25 parts by weight of water retaining agent hydroxypropyl methylcellulose ether, 0.15 parts by weight of retarder sodium gluconate and 95 parts by weight of water. The mineral filler is composed of talc powder, microsilica powder and fly ash in a weight ratio of 1:2:2.

[0056] The preparation method of the functionalized phase change material is as follows:

[0057] D1: 12.5 parts by weight of aluminum silicate fiber aerogel and 4.5 parts by weight of N-[(3-trimethoxysilyl)propyl]ethylenediaminetriacetic acid (CAS: 84127-79-7) were mixed and ball-milled at 600 rpm for 12 h; then added to 100 parts by weight of water, ultrasonically treated at 500 W and 30 kHz for 1.5 h, centrifuged after the end, and freeze-dried to obtain pre-treated aluminum silicate fiber aerogel; wherein the ball milling medium was 3 mm zirconia balls, and the ball-to-material ratio was 12:1;

[0058] D2: 3 parts by weight of titanium tetrachloride and 200 parts by weight of ethanol aqueous solution (mass percentage concentration of 90%) were mixed, and then 3.5 parts by weight of ammonia water (mass percentage concentration of 26.5%) were added dropwise, stirred at 72°C for 1.5 hours, cooled to room temperature after the stirring, and then 12 parts by weight of pre-treated aluminum silicate fiber aerogel were added, and ultrasonic treatment was performed at 500W and 30kHz for 1 hour. After the stirring, the mixture was allowed to stand for 12 hours, concentrated under reduced pressure to recover ethanol, and freeze-dried to obtain a composite aggregate;

[0059] D3: 7.5 parts by weight of polyvinyl alcohol and 2.5 parts by weight of stearyl alcohol (CAS: 112-92-5) are mixed, heated to melt under vacuum conditions, and then 5 parts by weight of composite aggregate are added. Vacuum impregnation is performed at 0.08 MPa and 60°C for 3 hours, and then cooled to room temperature to obtain the functionalized phase change material.

[0060] A method for preparing high-strength thermal insulation mortar, comprising the following steps:

[0061] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, functional phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are uniformly mixed, and then water is added and stirred at a speed of 80 rpm for 10 minutes to obtain the high-strength thermal insulation mortar.

[0062] Example 2

[0063] A high-strength thermal insulation mortar, comprising the following raw materials:

[0064] 40 parts by weight of silicate cement, 50 parts by weight of vitrified microspheres, 30 parts by weight of mineral fillers, 3 parts by weight of functionalized phase change materials, 1 part by weight of nano-montmorillonite, 0.5 parts by weight of dispersible latex powder, 0.2 parts by weight of air entraining agent sodium dodecylbenzene sulfonate, 0.1 parts by weight of water retaining agent hydroxypropyl methylcellulose ether, 0.1 parts by weight of retarder sodium gluconate and 90 parts by weight of water. The mineral filler is composed of talc, microsilica powder and fly ash in a weight ratio of 1:1:1.

[0065] The preparation method of the functionalized phase change material is the same as that of Example 1.

[0066] A method for preparing high-strength thermal insulation mortar, comprising the following steps:

[0067] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, functional phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are evenly mixed, and then water is added and stirred at a speed of 50 rpm for 15 minutes to obtain the high-strength thermal insulation mortar.

[0068] Example 3

[0069] A high-strength thermal insulation mortar, comprising the following raw materials:

[0070] 60 parts by weight of silicate cement, 70 parts by weight of vitrified microspheres, 40 parts by weight of mineral fillers, 7 parts by weight of functional phase change materials, 3 parts by weight of nano-montmorillonite, 1 part by weight of dispersible latex powder, 0.4 parts by weight of air entraining agent sodium dodecylbenzene sulfonate, 0.3 parts by weight of water retaining agent hydroxypropyl methylcellulose ether, 0.2 parts by weight of retarder sodium gluconate and 100 parts by weight of water. The mineral filler is composed of talc, microsilica powder and fly ash in a weight ratio of 1:3:3.

[0071] The preparation method of the functionalized phase change material is the same as that of Example 1.

[0072] A method for preparing high-strength thermal insulation mortar, comprising the following steps:

[0073] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, functional phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are uniformly mixed, and then water is added and stirred at a speed of 100 rpm for 5 minutes to obtain the high-strength thermal insulation mortar.

[0074] Example 4

[0075] A high-strength thermal insulation mortar, comprising the following raw materials:

[0076] 50 parts by weight of silicate cement, 60 parts by weight of vitrified microspheres, 35 parts by weight of mineral fillers, 5 parts by weight of phase change materials, 2 parts by weight of nano-montmorillonite, 0.8 parts by weight of dispersible latex powder, 0.3 parts by weight of air entraining agent sodium dodecylbenzene sulfonate, 0.25 parts by weight of water retaining agent hydroxypropyl methylcellulose ether, 0.15 parts by weight of retarder sodium gluconate and 95 parts by weight of water. The mineral filler is composed of talc powder, microsilica powder and fly ash in a weight ratio of 1:2:2.

[0077] The preparation method of the phase change material is:

[0078] 7.5 parts by weight of polyvinyl alcohol and 2.5 parts by weight of stearyl alcohol (CAS: 112-92-5) were mixed, heated to melt under vacuum conditions, and then 5 parts by weight of silica aerogel were added, and vacuum impregnation was performed at 0.08 MPa and 60°C for 3 hours, and then cooled to room temperature to obtain the phase change material. The silica aerogel used commercially available hydrophobic silica aerogel particles with a bulk density of 100-110 kg / m 3 , particle size 2.5-10mm.

[0079] A method for preparing high-strength thermal insulation mortar, comprising the following steps:

[0080] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are uniformly mixed, and then water is added and stirred at a speed of 80 rpm for 10 minutes to obtain the high-strength thermal insulation mortar.

[0081] Example 5

[0082] A high-strength thermal insulation mortar, comprising the following raw materials:

[0083] 50 parts by weight of silicate cement, 60 parts by weight of vitrified microspheres, 35 parts by weight of mineral fillers, 5 parts by weight of functionalized phase change materials, 2 parts by weight of nano-montmorillonite, 0.8 parts by weight of dispersible latex powder, 0.3 parts by weight of air entraining agent sodium dodecylbenzene sulfonate, 0.25 parts by weight of water retaining agent hydroxypropyl methylcellulose ether, 0.15 parts by weight of retarder sodium gluconate and 95 parts by weight of water. The mineral filler is composed of talc powder, microsilica powder and fly ash in a weight ratio of 1:2:2.

[0084] The preparation method of the functionalized phase change material is as follows:

[0085] D1: 3 parts by weight of titanium tetrachloride and 200 parts by weight of ethanol aqueous solution (mass percentage concentration of 90%) were mixed, and then 3.5 parts by weight of ammonia water (mass percentage concentration of 26.5%) were added dropwise, stirred at 72°C for 1.5 hours, cooled to room temperature after the stirring, and then 12 parts by weight of aluminum silicate fiber aerogel were added, and ultrasonic treatment was performed at 500W and 30kHz for 1 hour. After the ultrasonic treatment, the mixture was allowed to stand for 12 hours, concentrated under reduced pressure to recover ethanol, and freeze-dried to obtain a composite aggregate;

[0086] D2: 7.5 parts by weight of polyvinyl alcohol and 2.5 parts by weight of stearyl alcohol (CAS: 112-92-5) are mixed, heated to melt under vacuum conditions, and then 5 parts by weight of composite aggregate are added. Vacuum impregnation is performed at 0.08 MPa and 60°C for 3 hours, and then cooled to room temperature to obtain the functionalized phase change material.

[0087] A method for preparing high-strength thermal insulation mortar, comprising the following steps:

[0088] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, functional phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are uniformly mixed, and then water is added and stirred at a speed of 80 rpm for 10 minutes to obtain the high-strength thermal insulation mortar.

[0089] Example 6

[0090] A high-strength thermal insulation mortar, comprising the following raw materials:

[0091] 50 parts by weight of silicate cement, 60 parts by weight of vitrified microspheres, 35 parts by weight of mineral fillers, 5 parts by weight of functionalized phase change materials, 2 parts by weight of nano-montmorillonite, 0.8 parts by weight of dispersible latex powder, 0.3 parts by weight of air entraining agent sodium dodecylbenzene sulfonate, 0.25 parts by weight of water retaining agent hydroxypropyl methylcellulose ether, 0.15 parts by weight of retarder sodium gluconate and 95 parts by weight of water. The mineral filler is composed of talc powder, microsilica powder and fly ash in a weight ratio of 1:2:2.

[0092] The preparation method of the functionalized phase change material is as follows:

[0093] D1: 12.5 parts by weight of aluminum silicate fiber aerogel and 4.5 parts by weight of N-[(3-trimethoxysilyl)propyl]ethylenediaminetriacetic acid (CAS: 84127-79-7) were mixed and ball-milled at 600 rpm for 12 h; then added to 100 parts by weight of water, ultrasonically treated at 500 W and 30 kHz for 1.5 h, centrifuged after the end, and freeze-dried to obtain pre-treated aluminum silicate fiber aerogel; wherein the ball milling medium was 3 mm zirconia balls, and the ball-to-material ratio was 12:1;

[0094] D2: 3 parts by weight of titanium tetrachloride and 200 parts by weight of ethanol aqueous solution (mass percentage concentration of 90%) were mixed, and then 3.5 parts by weight of ammonia water (mass percentage concentration of 26.5%) were added dropwise, stirred at 72°C for 1.5 hours, cooled to room temperature after the stirring, and then 12 parts by weight of pre-treated aluminum silicate fiber aerogel were added, and ultrasonic treatment was performed at 500W and 30kHz for 1 hour. After the stirring, the mixture was allowed to stand for 12 hours, concentrated under reduced pressure to recover ethanol, and freeze-dried to obtain a composite aggregate;

[0095] D3: 10 parts by weight of polyethylene glycol 1500 are mixed, heated to melt under vacuum conditions, and then 5 parts by weight of composite aggregate are added, vacuum impregnated at 0.08 MPa and 60° C. for 3 hours, and then cooled to room temperature to obtain the functionalized phase change material.

[0096] A method for preparing high-strength thermal insulation mortar, comprising the following steps:

[0097] According to the raw material formula, silicate cement, vitrified microspheres, mineral filler, functional phase change material, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder are uniformly mixed, and then water is added and stirred at a speed of 80 rpm for 10 minutes to obtain the high-strength thermal insulation mortar.

[0098] Test Example 1

[0099] The high-strength thermal insulation mortar obtained in the above embodiment was cast in a conventional manner (ambient temperature 23°C, relative humidity 50%) to obtain a block sample with a length of 70.7mm×70.7mm×70.7mm. After pouring, the high-strength thermal insulation mortar was adjusted in an environment with a temperature of 23°C and a relative humidity of 50%, and a total of 28 days were spent from the start of pouring to the completion of adjustment. The compressive strength of the high-strength thermal insulation mortar obtained in the above embodiments 1, 4-5 was determined according to GB / T20473-2021 "Building Thermal Insulation Mortar". For each embodiment, 10 parallel samples were taken for testing and the average value was taken.

[0100] Table 1. Compressive strength of high-strength thermal insulation mortar

[0101] Compressive strength(MPa) Example 1 35.6 Example 4 27.3 Example 5 32.4

[0102] Test Example 2

[0103] The high-strength thermal insulation mortar obtained in the above embodiment was cast in a conventional manner (ambient temperature 23°C, relative humidity 50%) to obtain a block sample with a length of 10cm×10cm×2cm. After casting, the high-strength thermal insulation mortar was adjusted in an environment with a temperature of 23°C and a relative humidity of 50%, and a total of 28 days were spent from the beginning of casting to the completion of adjustment. The combustion grade of the high-strength thermal insulation mortar obtained in the above embodiments 1-4 was tested according to GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products". For each embodiment, 10 parallel samples were taken for testing and the average value was taken.

[0104] Table 2. Fire resistance of high-strength thermal insulation mortar

[0105] Combustion level Example 1 A Example 2 A Example 3 A Example 4 B1

[0106] Test Example 3

[0107] The high-strength thermal insulation mortar obtained in the above embodiment is cast in a conventional manner (ambient temperature 23°C, relative humidity 50%) to obtain a block sample with a length of 10cm×10cm×2cm. After casting, the high-strength thermal insulation mortar is adjusted in an environment with a temperature of 23°C and a relative humidity of 50%, and a total of 28 days are spent from the beginning of casting to the completion of adjustment. The thermal conductivity of the high-strength thermal insulation mortar obtained in the above embodiments 1-6 is measured according to GB / T 32064-2015 "Test method for thermal conductivity and thermal diffusivity of building materials by transient plane heat source". For each embodiment, 10 parallel samples are taken for testing and the average value is taken.

[0108] Table 3. Thermal conductivity of high-strength thermal insulation mortar

[0109] Thermal conductivity (W / (m·K)) Example 1 0.025 Example 2 0.031 Example 3 0.021 Example 4 0.052 Example 5 0.040 Example 6 0.036

[0110] It can be seen that the thermal insulation mortar of the present invention improves the thermal insulation performance of the mortar while ensuring the strength and bonding performance of the mortar through the unique raw material combination of silicate cement, vitrified microspheres, mineral fillers, functionalized phase change materials, nano-montmorillonite and dispersible latex powder. Among them, the thermal insulation mortars of Examples 1-3 are superior to Examples 4-6 in terms of thermal insulation performance, compressive strength and fire resistance. This is because the functionalized phase change materials used in Examples 1-3 are a combination of polyvinyl alcohol and stearyl alcohol as phase change materials, and are then encapsulated by nano-titanium dioxide hybrid aluminum silicate fiber aerogel as a composite aggregate. It has better compatibility and thermal stability. Adding it to the thermal insulation mortar can not only further improve the thermal insulation performance of the mortar, but also significantly improve the strength and fire resistance of the mortar. The composite aggregate has a large specific surface area. On the one hand, it has the advantages of low thermal conductivity and good thermal stability of aluminum silicate fiber aerogel (the aluminum silicate fiber aerogel with a three-dimensional pore structure in the composite aggregate can form a barrier in the mortar, reduce heat transfer, and assist in enhancing the thermal insulation effect). On the other hand, it can also play a skeleton support role and has excellent mechanical properties.

[0111] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A high-strength thermal insulation mortar, characterized in that: The raw materials include: silicate cement, vitrified microspheres, mineral fillers, functionalized phase change materials, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent, retarder and water; The preparation method of the functionalized phase change material is as follows: D1: mixing aluminum silicate fiber aerogel and N-[(3-trimethoxysilyl)propyl]ethylenediaminetriacetic acid for ball milling, then adding them into water for ultrasonic treatment, centrifuging them after the end, and freeze-drying them to obtain pre-treated aluminum silicate fiber aerogel; D2: Mix titanium tetrachloride and ethanol aqueous solution, then add ammonia water dropwise, heat and stir, cool after completion, add pretreated aluminum silicate fiber aerogel, perform ultrasonic treatment, let stand, reduce pressure and concentrate to recover ethanol, and freeze-dry to obtain composite aggregate; D3: Mix polyvinyl alcohol and stearyl alcohol and perform vacuum melting, then add composite aggregate and perform vacuum impregnation, and then cool to obtain the functionalized phase change material.

2. The high-strength thermal insulation mortar according to claim 1, characterized in that: The invention comprises the following raw materials: 30-80 parts by weight of silicate cement, 30-80 parts by weight of vitrified microspheres, 20-50 parts by weight of mineral filler, 1-10 parts by weight of functionalized phase change material, 0.5-5 parts by weight of nano-montmorillonite, 0.1-1.5 parts by weight of dispersible latex powder, 0.05-0.5 parts by weight of air entraining agent, 0.05-0.5 parts by weight of water retaining agent, 0.05-0.3 parts by weight of retarder and 50-150 parts by weight of water.

3. The high-strength thermal insulation mortar according to claim 1, characterized in that: The invention comprises the following raw materials: 40-60 parts by weight of silicate cement, 50-70 parts by weight of vitrified microspheres, 30-40 parts by weight of mineral filler, 3-7 parts by weight of functionalized phase change material, 1-3 parts by weight of nano-montmorillonite, 0.5-1 parts by weight of dispersible latex powder, 0.2-0.4 parts by weight of air entraining agent, 0.1-0.3 parts by weight of water retaining agent, 0.1-0.2 parts by weight of retarder and 90-100 parts by weight of water.

4. The high-strength thermal insulation mortar according to claim 1, characterized in that: The mineral filler is composed of at least two of talcum powder, microsilica powder and fly ash.

5. The high-strength thermal insulation mortar according to claim 1, characterized in that: The air entraining agent is at least one of sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, sodium rosin acid, and sodium α-olefin sulfonate.

6. The high-strength thermal insulation mortar according to claim 1, characterized in that: The water retaining agent is at least one of hydroxypropyl methyl cellulose ether, maltodextrin, starch ether, methyl cellulose and hydroxyethyl methyl cellulose ether.

7. The high-strength thermal insulation mortar according to claim 1, characterized in that: The retarder is at least one of sodium gluconate, sodium citrate, tartaric acid and calcium gluconate.

8. The method for preparing the high-strength thermal insulation mortar according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing silicate cement, vitrified microspheres, mineral fillers, functional phase change materials, nano-montmorillonite, dispersible latex powder, air entraining agent, water retaining agent and retarder according to the raw material formula, and then adding water for stirring to obtain the high-strength thermal insulation mortar.

Citation Information

Patent Citations

  • Novel heat-preservation mortar

    CN103693914A

  • Novel insulation mortar and preparation method thereof

    CN104163589A

  • A thermal insulation mortar and its preparation method

    CN108069660B

  • 3D printing thermal insulation mortar and preparation method and application thereof

    CN111517715A

  • Fireproof flame-retardant thermal insulation mortar and preparation method thereof

    CN111892353A